A review on the applications of PCM in thermal storage of solar energy. (2021) - Chaturvedi, Rishabh; Islam, Anas; Sharma, Kamal
Abstract: Renewable energy is the most promising one in current times and it this work a work on PCM and renewable energy has been discussed. Sustainable development and various heat storage methods are discussed in this paper. For certain green energy supplies, a vital energy source capable of substituting specifically or partially is solar energy, its only drawback is, that the solar electricity can be accessible during the day-time only. For solving this, TES (thermal energy storage) systems are used for retaining the energy in the day-time by consuming solar radiations. In this research, various strategies regarding thermal storage have been identified, that has been explored further by the addition of Phase changing materials (PCM), and they can be added successfully in almost all TES systems. Energy storage techniques have been explained in this paper for modern day combustibles for example gasoline, gas, etc. and this will be very beneficial in preserving climate and greenhouse gas emission elimination.